75 Prevalence and motivations of sexting behaviour among African American Youth. (9th June 2015) - Roche, Jessica; Epstein-Ngo, Quyen; Carter, Patrick; Konrath, Sara; Walton, Maureen; Zimmerman, Marc; Cunningham, Rebecca
Abstract : Statement of purpose: Sexting by youth has recently garnered much attention in popular media; and although some prior literature has begun to describe sexting experiences, limited research has been conducted among African American youth. Methods/approach: Participants 14–20 years old were screened at an urban Emergency Department based on home address, as part of a larger intervention study. Participants self-administered a computerised survey consisting of validated measures for dating violence (CADRI), substance use (ASSIST), social support (MSPSS), and mindfulness (CAMM). "Sexting, " defined as using digital media (cell phones, social media, etc.) to "send, receive, and post online sexually suggestive (sexy), nude, or nearly nude pictures or video, " was adapted from 6-measures used in prior literature. Bivariate and Multivariate analyses were conducted predicting "Sexting" behaviour Results: 335 youth were surveyed; 43.3% reported sexting behaviours/experiences in the past 2 months (55% female, 92% African American, 78% public assistance). Males were more likely to report sending (OR = 1.67) and posting sexually suggestive images of themselves (OR = 2.38), and were more likely to report having someone post these images of them online (OR = 2.22). Most reported sending/posting sexts to flirt (56.6%), with females more likely to endorse this behaviour (73.8%). Regression analyses found that physical dating violence (OR = 2.39), substance use (OR = 2.76), and more time on social network sites (OR = 1.09) were predictive of sexting behaviour; while higher mindfulness scores (OR = 0.97) and more social support (OR = 0.98) were protective against sexting involvement. Conclusions: Sexting is common among high-risk youth, and while a youth's motivation for sexting is often positive, "Sexting" behaviour is also associated with other high-risk behaviours, including dating violence and substance use. Additional research is needed to develop and implement potential interventions. Significance and contributions: This study of sexting experiences is the first, to our knowledge, to be conducted in a non-school-based, predominantly African American youth population.